Willingness to pay (WTP) for HIV and AIDS services in Africa: a descriptive thematic systematic review - John Bekiita Byabagambi; Mark Limmer; Bruce Hollingsworth (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background The African continent has the highest burden of HIV and AIDS, with its response to HIV and AIDS largely donor supported. However, in the face of declining donor support, alternative ways to sustainably support HIV and AIDS responses in Africa are paramount. This systematic review explores the willingness to pay (WTP) for HIV services in Africa as a potentially more sustainable HIV and AIDS service cost recovery approach. # Methods A comprehensive systematic search for literature was conducted in PubMed, EMBASE, Web of Science, and CINAHL and websites of HIV and AIDS organisations for studies published until 30 June 2023. Studies were included if they were about WTP, HIV and AIDS services, were conducted in Africa and were published in English. Studies were excluded if they used methods other than WTP and were not about an HIV service. JBI critical appraisal tools were used to assess for quality and risk of bias. Information on the HIV service, the study methods, and factors influencing WTP were extracted. A descriptive thematic analysis was undertaken to synthesise evidence. The findings are summarised in tables and graphs. # Results 5,141 records were identified and screened for eligibility from the initial search. After title and abstract screening and removing duplicates, twenty-three articles from 10 countries with 20,780 study participants were included in the final review. There is an uneven distribution of WTP studies across different types of HIV services and across countries. There is evidence of a willingness to pay for HIV services, with the proportion of people reported in individual studies that are willing to pay ranging from 34.3% to 97.1%. However, in most studies (77.3%, 17/22), the amount people are willing to pay cannot cover the full-service cost in an open market. Factors associated with WTP include socio-economic status, beliefs, and knowledge about HIV services. # Conclusions This systematic review presents evidence of cost recovery from HIV programs. The main finding is that other resources, beyond out-of-pocket payments, are needed to meet the total cost of any service. This has implications for providing (non-donor-funded) services on a sustainable level in the long term. In interpreting the findings of this study, limitations such as excluding papers not published in English need to be considered. **Registration**: PROSPERO, CRD42021275215.